Influence of admission plasma glucose level on short- and long-term prognosis in patients with ST-segment elevation myocardial infarction - Mladenović Violeta; Zdravković Vladimir; Jović Marina; Vučić Rada; Irić-Ćupić Violeta; Rosić Mirko A. (Vojnosanitetski Pregled)
Background/Aim. Hyperglicemia is common in patients with ST-elevation myocardial infarction (STEMI) and is associated with high risk of mortality and morbidity. Relationship between admission plasma glucose (APG) levels and mortality in diabetic and nondiabetic patients with STEMI needs further investigation. The aim of this study was to analyse the short- and longterm prognostic significance of APG levels in patients with STEMI with and without diabetes. Methods. This study included 115 patients with STEMI, 86 (74,8%) nondiabetic and 29 (25,2%) dibaetic patients, in which we performed a prospective analysis of the relationship between APG levels and shortand long-term mortality. Results. Comparison of APG levels between nondiabetic (8.32 ± 2.4 mmol/L) and diabetic (10.09 ± 2.5 mmol/L) patients showed statistically significantly higher average APG levels in diabetic patients (p = 0.001). In all patients observed who died either after one month or one year after STEMI, average APG values were significantly higher in comparison with those in survived patients. There was no statistical significance in average APG levels in the diabetic patients with STEMI who died after one month and those who survived (10.09 ± 2.68 vs 10.0 ± 2.51 mmol/L, respectively; p = 0.657), as well as those who died after one year and those who survived (10.1 ± 1.92 vs 10.09 ± 2.8 mmol/L, respectively; p = 0.996). There was, however, statistical significance in average APG levels in the nondiabetic patients with STEMI who died after one month and those who survived (9.97 ± 2.97 vs 7.91 ± 2.08 mmol/L, respectively; p = 0.001), as well as those who died after one year and those who survived (9.17 ± 2.49 vs 7.84 ± 2.24 mmol/L, respectively; p = 0.013). Conclusion. Acute hyperglicemia in the settings of STEMI worsenes the prognosis in patients with and without diabetes. Our study showed that nondiabetic patients with high APG levels are at higher risk of mortality than patients with a known history of diabetes.